More than bad news. A critical review of studies on media and war (2015)
This paper is a state of the art on the relationship media-war. It offers a critical review of the studies about this relationship in contexts of armed confrontations, where authorities have tried to exert political influence on journalists, media and public opinion to impose a hegemonic vision for the cause of war. The text emphasizes on the nature of mediatic representations of modern warfare, from a perspective that stresses both the coverage of the war and their regimes of visibility. Finally, it shows the main trends in studies onn the coverage of the armed conflict in Colombia